Mid-sized felids threatened by habitat degradation in Southeast Asia - Decœur, Henri (2023)
Deforestation and poaching in Southeast Asia have driven a stark decline in the region's apex predators, including large felids like tigers and leopards. Meanwhile, some small felids thrive in the region's human-modified landscapes. The extent to which medium-sized felids cope with anthropogenic disturbances remains poorly understood, but this information is crucial for the conservation of threatened felids and key trophic interactions that maintain high-diversity food webs. Here, we use the largest camera-trap dataset from Southeast Asia to conduct a multi-scale synthesis of the habitat associations of two cryptic felids, the Near-Threatened Asiatic golden cat (Catopuma temminckii) and the Endangered bay cat (Catopuma badia). Unlike many mesopredators, both species exhibited poor tolerance to habitat degradation (i.e. selective logging, edges or fragmentation). The golden cat was positively associated with forest patch size and elevation, and negatively associated with degraded forests, and the bay cat was negatively associated with human population density. Our habitat suitability model suggests that ongoing forest fragmentation and degradation have critically reduced suitable habitat for the golden cat, giving reason to suspect a population decline that calls for a revision of the species' IUCN Red List status to Vulnerable. There is also evidence that the bay cat may be more widely distributed in Borneo than previously thought, including in areas currently threatened by deforestation. Our results indicate both species face a high risk of becoming extirpated from many of the region's remaining forests. In areas where apex predators have been extirpated, these charismatic mid-sized felids can become umbrella species to protect forests with high biodiversity value.